ANALISIS KASUS ATAS PUTUSAN MAHKAMAH AGUNG NO. 189 PK/PDT/2009 TENTANG KEABSAHAN KEPEMILIKAN DAN PERALIHAN HAK ATAS TANAH - EDWIN ROLIN TAMPUBOLON (PREMISE LAW JURNAL, 2016)
Nowadays a land title, possessed simultaneously by two different persons or corporations, is frequently found so that all construction work has to be stopped and abandoned because until the land title is certain, it will remain a conflict. The conflict is resulted from both owners who acknowledge having the proof of the title of a same plot of land. Such conflict can be observed in a case mentioned in the the Supreme Court’s Ruling No.189 PK/PDT/2009. The research was a descriptive analysis using judicial normative method or legal library research. The role of the Judge in settling the case of the land title validity was to carry out his function and authority honestly and fairly, in which he had to be able to interpret the prevailing law actually and he also had to be brave to create a new law as a legal form. Based on the Judge’ consideration in the Verdict No.189 PK/PDT/2009, it was pronounced that SHM 6036 Cilandak was void because SHM 897/Cilandak had been transferred in Deed 16 and Deed 17. SHM 897 was taken by the owner. It was manipulated to be declared missing, reported to the Police and requested to be reissued with a new SHM.. Consequently, by the objection of the Judge of the Supreme Court in the Ruling No.189 PK/PDT/2009, the Title Certificate No. 6036/Cilandak possessed by the claimant was annulled and he lost his right over the land. The significance of the Verdict on the defendant was that the Certificate No.897/Cilandak possessed by the defendant was pronounced valid and he has the right to occupy and own the land. Keywords: Land Title Transfer, Double Title, Ruling